Alternative medicine - a replacement or an adjunctive for conventional therapy of chronic pain - Adrian Bobrzyk; Weronika Kamińska; Grzegorz Łyko; Maria Antos; Piotr Bator; Angelika Wawryszuk; Maciej Rumian; Weronika Makowska; Krystian Rachwał (Journal of Education, Health and Sport, 2023)
Introduction and purpose: